Vesiculation from Pseudomonas aeruginosa under SOS - Reshma Maredia; Navya Devineni; Peter Lentz; Shatha F. Dallo; JiehJuen Yu; Neal Guentzel; James Chambers; Bernard Arulanandam; William E. Haskins; Tao Weitao (The Scientific World Journal)
Bacterial infections can be aggravated by antibiotic treatment that induces SOS response and vesiculation. This leads to a hypothesis concerning association of SOS with vesiculation. To test it, we conducted multiple analyses of outer membrane vesicles (OMVs) produced from the Pseudomonas aeruginosa wild type in which SOS is induced by ciprofloxacin and from the LexA noncleavable (lexAN) strain in which SOS is repressed. The levels of OMV proteins, lipids, and cytotoxicity increased for both the treated strains, demonstrating vesiculation stimulation by the antibiotic treatment. However, the further increase was suppressed in the lexAN strains, suggesting the SOS involvement. Obviously, the stimulated vesiculation is attributed by both SOS-related and unrelated factors. OMV subproteomic analysis was performed to examine these factors, which reflected the OMV-mediated cytotoxicity and the physiology of the vesiculating cells under treatment and SOS. Thus, SOS plays a role in the vesiculation stimulation that contributes to cytotoxicity.